UNDERSTANDING THE NEXUS OF CLIMATE CHANGE AND URBAN POVERTY: DOMINANT DISCOURSES IN ACADEMIC PUBLICATIONS - Lestari, Dian; Luhur, Andi (CosmoGov: Jurnal Ilmu Pemerintahan, 2025)
The purpose of this study is to examine recurring themes in publications on the relationship between urban poverty and climate change. CiteSpace and RStudio software are utilised in this study’s bibliometric analysis to retrieve articles from the Scopus database on the relationship between urban poverty and climate change. CiteSpace and RStudio tools were utilised to analyse the data and create visualisations, examining research patterns and topic developments in the areas of urban poverty and climate change governance. The research results identified 13 clusters, with the largest cluster being "informal urban settlements" which had 73 members and a silhouette value of 0.824. This settlement is labeled as an informal urban settlement by LLR, a case study by LSI, and discipline (3.73) by MI. Although they contribute the least to greenhouse gas emissions, people experiencing poverty are the group that is most affected, according to Campbell-Lendrum, the author of the mentioned article. Due to the rapid economic growth and concurrent urbanisation of developing nations, cities in these regions will be more susceptible to the health risks associated with climate change while also contributing to a growing number of issues. Scholars have not focused on the relationship between the impact of climate change and urban poverty because the keywords linking the two issues are not addressed in this study, which makes it intriguing.gb777